2016
DOI: 10.1002/jcb.25798
|View full text |Cite
|
Sign up to set email alerts
|

Increase of Intracellular Cyclic AMP by PDE4 Inhibitors Affects HepG2 Cell Cycle Progression and Survival

Abstract: Type 4 cyclic nucleotide phosphodiesterases (PDE4) are major members of a superfamily of enzymes (PDE) involved in modulation of intracellular signaling mediated by cAMP. Broadly expressed in most human tissues and present in large amounts in the liver, PDEs have in the last decade been key therapeutic targets for several inflammatory diseases. Recently, a significant body of work has underscored their involvement in different kinds of cancer, but with no attention paid to liver cancer. The present study inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 45 publications
1
24
0
1
Order By: Relevance
“…This, in turn, led to de-phosphorylation of the signal transducer and activator of transcription 3 (STAT3) resulting in repressed STAT3 target genes and inhibition of hepatocarcinogenesis. Additionally, another study utilizing PDE4 inhibitors to increase intracellular cAMP levels reported that cAMP interfered with cell cycle progression (decreased availability of cyclin A and increased expression of p21) and inhibited cell proliferation in a hepatocarcinoma-derived cell line (HepG2 cells) [119]. …”
Section: The Role Of Camp In Nafldmentioning
confidence: 99%
“…This, in turn, led to de-phosphorylation of the signal transducer and activator of transcription 3 (STAT3) resulting in repressed STAT3 target genes and inhibition of hepatocarcinogenesis. Additionally, another study utilizing PDE4 inhibitors to increase intracellular cAMP levels reported that cAMP interfered with cell cycle progression (decreased availability of cyclin A and increased expression of p21) and inhibited cell proliferation in a hepatocarcinoma-derived cell line (HepG2 cells) [119]. …”
Section: The Role Of Camp In Nafldmentioning
confidence: 99%
“…Melatonin (2.5 mM) incubation of HepG2 cells could reduce cAMP level that further counteracted using luzindole (Carbajo‐Pescador et al, ), thereby suppression of MT1 receptor prevents cytotoxic and cytostatic effects of melatonin on HepG2 cells, possibly contributed to alterations in the intracellular concentrations of cAMP (Ordoñez et al, ). CAMP is also inhibited by type 4 cyclic nucleotide phosphodiesterases (PDE4) that is a main member of a superfamily of enzymes (PDE) responsible for inhibition of cAMP, p27 kip1 , p21, and p53 (Massimi et al, ). P27 is contributed to inhibition of cell cycle progression from G0 to G1 by regulating cdk2‐cyclin complex (cyclin A) (Massimi et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…CAMP is also inhibited by type 4 cyclic nucleotide phosphodiesterases (PDE4) that is a main member of a superfamily of enzymes (PDE) responsible for inhibition of cAMP, p27 kip1 , p21, and p53 (Massimi et al, ). P27 is contributed to inhibition of cell cycle progression from G0 to G1 by regulating cdk2‐cyclin complex (cyclin A) (Massimi et al, ). As it has been previously discussed, melatonin is capable of inhibiting cell arrest in the G0/G1 phase of cell cycle (Carbajo‐Pescador et al, ) and increasing the rate for expressions of p21 (Carbajo‐Pescador et al, ) and p53 (Martín‐Renedo et al, ) (Figure ), so it seems that this indoleamine possibly regulates most of the functions for PDE4 in HepG2 cells.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, whether this interaction may be a novel therapeutic target to alter cancer tumor growth, angiogenesis and metastasis, without affecting normal cell physiology deserves special attention. Then, it would not be a surprise the suggestion of using CCBs in combination with pharmaceuticals which increase cAMP to inhibit cancer progression [8,9,15]. Therefore, the current knowledge about regulation of intracellular Ca 2+ and cAMP homeostasis in cancer tumor cells, and the search for new pharmacological strategies to control these intracellular messengers may be able to lead the development of new pharmacological and non-pharmacological strategies that specifically alter tumor growth, angiogenesis and metastasis, without affecting normal cell physiology.…”
Section: Role Of Ca 2+ /Camp Signalling In Cancer Progressionmentioning
confidence: 99%
“…In addition to Ca 2+ , cAMP has been implicated in the regulation of cancer progression [15]. From this concept in mind, phosphodiesterase IV inhibitors like rolipram, which increase cAMP have been proposed as potential adjuvant, chemotherapeutic or chemopreventive agents in hepatocellular carcinoma [15].…”
Section: Introductionmentioning
confidence: 99%